Dynamics and efficacy of sulfentrazone, flumioxazin, and isoxaflutole herbicides applied on eucalyptus harvest residues - Carbonari, Caio Antonio [UNESP]; Gomes, Giovanna Larissa Gimenes Cotrick [UNESP]; Krenchinski, Fábio Henrique [UNESP]; Simões, Plinio Saulo [UNESP]; Batista de Castro, Edicarlos [UNESP]; Velini, Edivaldo Domingues [UNESP] (Springer Nature, 2020)
Eucalyptus harvests generate residues that remain on the soil and affect the efficacy of preemergent herbicides in the following planting cycle. The objective of this work was to evaluate the dynamics of flumioxazin, sulfentrazone, and isoxaflutole herbicides applied on different amounts and compositions of eucalyptus harvest residues subjected to different rainfall depths; and evaluate the weed control effectiveness of these herbicides when applied under these conditions. A LC–MS/MS system was used for the evaluations and the results showed that a cumulative rainfall of 50 mm was sufficient for the maximum removal of herbicides from the eucalyptus residues, regardless of the residue composition. The amount of the flumioxazin, sulfentrazone, and isoxaflutole herbicides that reached the soil was lower in the treatment with the highest amount of eucalyptus harvest residue used (40 Mg ha−1). The greatest amount of herbicide reaching the soil was found with the use of 15 Mg ha−1 of residues without presence of bark. The highest amount of residue used (40 Mg ha−1) reduced the control of Brachiaria decumbens by sulfentrazone and isoxaflutole. The control of Commelina benghalensis was inefficient (> 80%) in the treatment with 15 Mg ha−1 of residues without barks, regardless of the herbicide. Sulfentrazone controlled Ipomoea grandifolia (> 90%) under the evaluated residue conditions. Spermacoce latifolia and Sida rhombifolia were controlled by all herbicides in the evaluated residue conditions. Isoxaflutole controlled Panicum maximum in all residue conditions. The choice between the herbicides depends on the residue condition, rainfall regime, and weed species to be controlled.
Keywords: Brachiaria decumbens; Herbicide dynamics; Ipomoea grandifolia; Panicum maximum; Preemergent herbicides; Soil cover